Introductory econometrics : a modern approach / Jeffrey M. Wooldridge. - Wooldridge, Jeffrey M., 1960- (Cengage, 2025)
Wooldridge uses a systematic approach motivated by the major problems facing applied researchers. This text provides important understanding for empirical work in many social sciences, as well as for carrying out research projects.